The Effectiveness of Teachers’ Job Performance Assessment in the Schools of Al-Batinah North Governorate, Sultanate of Oman in Their Perspective - Al-Jahwari, Mohammed Salim Ali (Journal of Educational and Psychological Sciences, 2023)
This study aimed to investigate the effectiveness of teachers' performance assessment in the Schools of Al-Batinah North Governorate, Sultanate of Oman, and find differences attributed to the variables of (gender, job title, academic qualification, and years of service). The research used the descriptive survey approach and made a questionary that consisted of (30) phrases of four fields for a sample of (260) male and female teachers. The results showed that the total average of the effectiveness of performance assessment was (3.29 out of 5) with a moderate grade. In terms of the fields, the objectives showed the highest average of (3.70) followed by significance (3.67), and then followed by feedback (3.42) in the third place to reflect a (high) grade of all of them. On the other hand, the last place was occupied by obstacles with an average of (2.36) and a (poor) grade. No difference level of (α≤0.05) attributed to the study variables and the study fields, except the first field, the objectives assessment, according to gender in favor of females. No difference level of (α≤0.05) for the variables in the study fields, except the second field of assessment significance according to the variable of job title in favor of senior teachers. No differences level of (α≤0.05) for the variable of academic qualification, except the fourth assessment obstacles in favor of bachelor's degree holders. No differences level of (α≤0.05) for the years-of-experience variable in the fields of the study. The research recommended aligning performance and rewards, engaging individuals in the assessment process, and making use of technology to evaluate performance, Further studies are suggested.
Keywords: Effectiveness; Occupational Performance Evaluation; Teachers; Al-Batinah North; Sultanate of Oman